Conceptualization and model development of customer‐to‐customer encounter quality (CCEQ) in service settings. Issue 6 (26th April 2018) - Kim, Hyun Sik; Lee, Jun Youb; La, Suna; Choi, Beomjoon
Abstract: Despite interests from many researchers, the conceptualization and measurement of customer‐to‐customer encounter quality (CCEQ) have mostly remained untapped. The present study aims to develop a conceptual framework to manage the impact of other customers on the focal customers' service experience based on the perceived service quality framework. In Study 1, the authors employed critical incident technique to establish a multilayered factor structure of CCEQ consisted of three primary categories: customer‐to‐customer hedonic quality, customer‐to‐customer utilitarian quality, and customer‐to‐customer normative quality. In Study 2, the authors examined reliability and validity of the CCEQ model by using comprehensive confirmatory factor analyses and structural equation modeling. The results support the conceptualization of CCEQ proposed in Study 1. As an initial work as to the conceptualization and measurement of CCEQ model, this study provides theoretical and managerial insights into other customers' influence on focal customers' overall evaluation of service experiences.